Perceptions of Hope Among Bereaved Caregivers of Cancer Patients Who Received Early Palliative Care: A Content and Lexicographic Analysis. (4th February 2022) - Bigi, Sarah; Ganfi, Vittorio; Borelli, Eleonora; Potenza, Leonardo; Artioli, Fabrizio; Eliardo, Sonia; Mucciarini, Claudia; Cottafavi, Luca; Cruciani, Massimiliano; Cacciari, Cristina; Odejide, Oreofe; Porro, Carlo Adolfo; et al.
Abstract: Background: Oncologists' fear of taking away hope from patients when proposing early palliative care (EPC) is a barrier to the implementation of this model. This study explores hope perceptions among bereaved caregivers of onco-hematologic patients who received EPC. Materials and Methods: Open-ended questionnaires were administered to 36 primary caregivers of patients who received EPC (26 solid and 10 hematologic cancer patients; mean age: 51.4 years, range age: 20-74), at 2 cancer centers, 2 months to 3 years after a patient death. Definitions of hope in the caregivers' narratives were analyzed through a directed approach to content analysis. Results were complemented with automated lexicographic analysis. Results: Caregivers perceived hope mainly as resilience and as expectations based on what they were told about the patients' clinical conditions. Their hope was bolstered by trusting relationships with the healthcare teams. EPC interventions were recalled as the major support for hope, both during the illness and after the death of the patient. The automated quantitative lexical analysis provided deeper insights into the links between hope, truth, and trust. Conclusions: Our findings suggest that telling the truth about an incurable onco-hematologic disease and beginning EPC might be the combination of factors triggering hope in the setting of incurable cancer. Abstract : Oncologists' fear of taking away hope from patients when proposing early palliative care is a barrier to the implementation of this model. This article explores hope perceptions among bereaved caregivers of patients with cancer who had received early palliative care.